Dijital kayıt ve konvansiyonel ölçü yöntemleri ile üretilen restorasyonların marginal ve internal uyumlarının in vitro olarak incelenmesi - Özsürmeli, Halis (My University, 2019)
Amaç: Bu çalışmanın amacı; dijital kayıt ve konvansiyonel ölçü yöntemleri ile üretilmiş farklı türdeki seramik kuronların ortalama marjinal ve internal aralık değerlerinin elde edilmesi ve elde edilen bu değerlerin karşılaştırılmasıdır. Gereç ve Yöntemler: Periodantal nedenler ile çekilmiş, çürüksüz, on adet molar diş prepare edilmiştir. Farklı ölçü ve üretim yöntemleri ile 60 adet restorasyon yapılmıştır. Silikon replika yöntemi ile marjinal ve internal aralık değerlendirmesi yapılmıştır. İstatistiksel analizler için Mann-Whitney U ve Kruskal – Wallis testleri kullanılmıştır (p <0.05). Bulgular: Farklı ölçü ve üretim yöntemleri arasında istatistiksel olarak anlamlı farklılıklar bulundu. En düşük ortalama marjinal aralık değeri, indirekt dijital-monolitik zirkonya grubunda (31.13 um) ve en yüksek ortalama aralık değeri indirekt dijital-lityum disilikat grubunun okluzal bölgesinde (90.09 um) görüldü. Sonuçlar: Çalışmamıza dahil edilen restorasyonların ortalama marjinal ve internal aralık değerleri (31.13-90.09µm) arasındadır. Test edilen restorasyonların ortalama marjinal ve internal aralıkları klinik olarak kabul edilebilir seviyededir.

Purpose: The purpose of this study was to compare the marginal and internal gap values of different types of ceramic crowns produced by digital and conventional impression methods. Materials and nethods: Ten non-carious extracted human teeth were prepared, and 60 restorations were made with different impression and production methods. Silicone replicas were obtained for marginal and internal gap evaluation. Statistical analyses were performed using Mann–Whitney U and Kruskal–Wallis tests (p < 0.05). Results: Statistically significant differences were found among various impression and production methods. The smallest gap value was shown by the monolithic zirconia indirect digital scanning group (31.13 µm), and the largest for the lithium disilicate indirect digital scanning group (90.09 µm). Conclusion: Among the restorations included in our study, the marginal and internal gap values were 31.13–90.09 µm. The marginal and internal discrepancies of the tested materials were considered clinically acceptable.
Keywords: and 60 restorations were made with different impression and production methods; and the largest for the lithium disilicate indirect digital scanning group (90.09 µm). Conclusion: Among the restorations included in our study; digital vs. conventional impression; digital vs. conventional workflows; dijital ve konvansiyonel iş akışları; dijital ve konvansiyonel ölçü Direct digital scanning; Diş; Diş hastalıkları; Health; indirect digital scanning; indirekt dijital tarama; marginal gap; marjinal aralık; Materials and nethods: Ten non-carious extracted human teeth were prepared; Purpose: The purpose of this study was to compare the marginal and internal gap values of different types of ceramic crowns produced by digital and conventional impression methods; Sağlık; Silicone replicas were obtained for marginal and internal gap evaluation; Statistical analyses were performed using Mann–Whitney U and Kruskal–Wallis tests (p < 0.05). Results: Statistically significant differences were found among various impression and production methods; the marginal and internal gap values were 31.13–90.09 µm. The marginal and internal discrepancies of the tested materials were considered clinically acceptable.direkt dijital tarama; The smallest gap value was shown by the monolithic zirconia indirect digital scanning group (31.13 µm); Tooth; Tooth diseases